Analisis Implementasi Kebijakan Pembelajaran Jarak Jauh Program Diploma IV Pada Masa Pandemi Covid 19 di Sekolah Tinggi Ilmu Pelayaran - Susiwi Rahayu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
At the start of the COVID-19 pandemic, all aspects of life were changed, including education. Distance learning is now preferred over face-to-face. The purpose of this study is to evaluate how the distance learning policy is implemented at the College of Shipping during the COVID-19 pandemic. This study also looks at the factors that support and hinder the implementation of the policy, as well as the strategies needed. In this study, a descriptive qualitative method was used. The informants in this study included Structural Officials as Policy Makers, Functional Officials, Lecturers, and Cadets working in policy implementation. This research collected data through observation and interviews. George C Edward III's theory was used as a reference, which states that policy implementation is influenced by four (4) factors: communication, resources, disposition, and bureaucratic structure. The results showed that, during the COVID-19 pandemic, the distance learning policy of the Diploma IV program at the College of Shipping was implemented quite well. However, there are shortcomings in its implementation. Supporting factors, such as the implementation of distance learning in an effort to accelerate the handling of the Covid-19 outbreak, are very helpful. The distance learning policy is considered the best option to maintain education in the midst of a pandemic. The commitment of leaders and communication with implementing staff is good enough. One thing that hinders is the lack of coordination between implementing staff (bureaucracy) when tracking the implementation of distance learning. This is because the SOP for distance learning is not yet available. Lecturers and cadets still complain about the internet network that sometimes experiences delays and sound that suddenly disappears, which disrupts the delivery of materials and consumes resources. Lecturers also complain about the skills of cadets in using simulator equipment, Lab Workshop, and other simulators.